Genome-wide scan in Portuguese Island families implicates multiple loci in bipolar disorder : fine mapping adds support on chromosomes 6 and 11 - Pato, Carlos N. (2017)
Submitted by Célia Barreto Carvalho (celia.mo.carvalho@uac.pt) on 2017-01-02T16:46:29Z No. of bitstreams: 1 43 Pato_et_al-2004-American_Journal_of_Medical_Genetics_Part_B-_Neuropsychiatric_Genetics.pdf: 149281 bytes, checksum: d892a6cbc48ddbd406782e21e73cb019 (MD5)